1954
DOI: 10.1099/00221287-10-3-353
|View full text |Cite
|
Sign up to set email alerts
|

Glucose utilization by Streptomyces griseus

Abstract: SUMMARY: Glucose utilization by a strain of Streptomyces griseus was studied. Under highly aerobic conditions, glucose was converted mainly to structural material and CO,, but under restricted aeration, lactic acid was formed. Pyruvic acid was also formed during the stages of most rapid growth. The metabolism of glucose was dependent upon the presence of phosphate, and the optimal hydrogenion concentration for both glucose oxidation and the rate of disappearance of inorganic phosphate was about pH 7. Phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The acidosis and developmental defect of BZ2, similar to those of most other bald mutants, was dependent on glucose. Previous studies have shown that organic acid excretion reflects imbalance between glycolysis and TCA cycle activities (13) and can be induced by oxygen limitation (12). The citrate synthase mutant consumed glucose at slightly higher rates and was unable to oxidize glycolytic products via the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The acidosis and developmental defect of BZ2, similar to those of most other bald mutants, was dependent on glucose. Previous studies have shown that organic acid excretion reflects imbalance between glycolysis and TCA cycle activities (13) and can be induced by oxygen limitation (12). The citrate synthase mutant consumed glucose at slightly higher rates and was unable to oxidize glycolytic products via the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In the present results, lactic acid accumulates during the entire growth phase. Although Streptomycetes are classified as strictly aerobic, their tendency to flocculate makes that the inside of the clumps grow probably micro-aerobically and produce lactate (Hockenhull et al, 1954;Borodina et al, 2005). Succinate production could also be caused by this oxygen limitation inside the kernels of the flocs but equally well may result from an imbalance of the carbon fluxes in the TCA cycle as shown by the WT experiment supplemented with 15 g/L casamino acids.…”
Section: Overflow Metabolism During Growth On Nmmp Supplemented With mentioning
confidence: 95%
“…The presence of lactate dehydrogenase in the sequenced genome of S. coelicolor A3(2) indicates that the organism should be capable of having a fully operational fermentative metabolism with lactate as a key fermentation product. Indeed, excretion of lactate has been observed for Streptomyces griseus grown under microaerophilic conditions (Hockenhull et al 1954). Two reasons were suggested to explain the anaerobic Streptomyces paradox: either the organisms are sensitive to the fermentation products or/and there are some essential reactions that require oxygen.…”
Section: Anaerobic Growthmentioning
confidence: 99%